The influence of a cyclic loading history on soil-geogrid interaction under pullout condition. Issue 4 (August 2019) - Cardile, G.; Pisano, M.; Moraci, N.
Abstract: The knowledge of soil-geosynthetic interface behaviour is a key point in the design of geosynthetic-reinforced soil structures. The pullout ultimate limit state can be reproduced conveniently by means of pullout tests performed with large-size laboratory apparatuses, which allow studying the interaction mechanisms that develop in the anchorage zone. During the service life of geosynthetic-reinforced soil structures, reinforcements may be subjected to long-term cyclic vehicular loads or short-term seismic loads in addition to dead loadings, such as the structure's self-weight and other sustained loads. In order to study the influence of a cyclic loading history (a sinusoidal function with fixed amplitude A, number of cycles N and frequency f ) on the post-cyclic peak pullout resistance, the writers carried out a series of multi-stage pullout tests on a high density polyethylene extruded uniaxial geogrid embedded in a compacted granular soil for different vertical effective stress σ ′v values. Moreover, the stability of the soil-geosynthetic interface from a point of view linked to the cyclic loading application has also been investigated. Test results showed that the design pullout resistance parameters are affected by the applied cyclic loading history for specific combined conditions ( A, N and σ ′v ) and it should be taken into account for designing geosynthetic reinforced soil structures.